Analisis Karakteristik Pergerakan Moda Transportasi Pengangkut Bawang Merah Kabupaten Enrekang - Fiqri Suparman; Hakzah Hakzah; Misbahuddin Misbahuddin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Land transportation as a means of inter-city transportation has the advantage of being able to distribute people and goods with a larger capacity and relatively cheaper costs. The aim of this research is to determine the characteristics of onion transportation, performance, distribution time and the purpose of distributing the onion harvest in Enrekang Regency. This research used a quantitative method, which was carried out for 1 month, namely in September-October 2022 in Enrekang Regency, South Sulawesi, using SPSS analysis. The results of the research show that the characteristics of the 240 respondents were all men, with the most widely used vehicle brand being the Mitsubishi 4-wheeled type (medium truck), the most frequent distribution time range was between 10-15 times a month with an average speed of 50- 60 km/hour, departure time between 10:00 – 15:00 WITA, and arriving around 15:00 – 18:00 WITA, distance over 100 Km, and the longest loading time is over 120 minutes, with the aim of distribution most often to exporters with a percentage of 57.08%, while for distribution areas outside Enrekang Regency the most frequently is Parepare City with a percentage of 46.25%.